Treatment of Spastic quadriplegia resulting from hypoxia in newborn through body engineering technique-hand therapy Case Report Described by Parents: Qualitative study (The International Journal for Scientific Research, 2024)
Objectives: Summary of Case Report on Spastic quadriplegia accompanied by several disabilities. Treatment with Body Engineering/Hand Therapy. This case report describes the successful treatment of a 4 years old girl who was diagnosed with Spastic quadriplegia and global developmental delay accompanied with relapse, slurred speech, and cognitive delay resulting from hypoxia during child birth. To report a case of a girl  who suffered Spastic quadriplegia, seizures, and delay in speech and perception due to  hypoxia and to highlights the critical role of body engineering techniques for the rehabilitation of children with similar cases.Methods: An informed case report was given by from the child's parents. Functional recovery was achieved through a customized rehabilitation plan according to the body engineering / hand therapy techniquesWe highlight:-Medical Management for such cases.-A rehabilitation plan based on body engineering/ hand therapy techniques that led to complete recovery.-Satisfaction of the patient's parents after treatment.Results: Treating the patient through body engineering (hand therapy) and rehabilitating him for a full year led to the appearance of signs of clinical and radiographic improvement.Conclusions: Hypoxia-induced spastic quadriplegia often results in multiple disabilities, as seen in this case. Early intervention using body engineering techniques can lead to significant improvements in physical and cognitive functions. Continuous monitoring and rehabilitation are recommended to sustain progress and prevent relapses (Odding et al., 2006). Based on the provided information, body engineering and hand therapy have proven to be highly effective in rehabilitating a girl with hypoxia-induced cerebral palsy. Through a comprehensive rehabilitation program, the patient's physical, cognitive, and communication abilities have significantly improved. This case report underscores the importance of early intervention in maximizing outcomes for children with spastic quadriplegia. By providing ongoing support and tailoring rehabilitation programs to individual needs, it is possible to help these children reach their full potential, aligning with the World Health Organization's definition of rehabilitation as a process to improve performance and reduce disability.
Keywords: Hypoxia-induced spastic quadriplegia; Body engineering; Rehabilitation; Motor skills; Cognitive function; Hand therapy; Cerebral palsy